Invincible (2003), volume 18 ebook The death of everyone. - Kirkman, Robert (Invincible (2003), 2015)
Mark Grayson's entire life as a superhero, all he's learned, all he's endured, it's all been leading to this one moment. Will he become the hero he was meant to or will he choose... a DIFFERENT path? Collects issues #97-102 of the greatest super hero comic in the universe.. Author: Robert Kirkman. Illustrator: Ryan Ottley, Cliff Rathburn, John Rauch . 2013 Robert Kirkman, LLC, Cory Walker and Ryan Ottley.